Deeper burning in a boreal fen peatland 1‐year post‐wildfire accelerates recovery trajectory of carbon dioxide uptake. Issue 3 (8th January 2021) - Morison, Matthew; van Beest, Christine; Macrae, Merrin; Nwaishi, Felix; Petrone, Richard
Abstract: Peatlands contain a globally significant store (30%) of soil carbon (C). Within the Canadian Western Boreal Plains, where peatlands are a dominant feature, the climate is becoming warmer and drier, coupled with an increase in forest fire incidence. The response of peatlands to forest fire is likely to be a key determinant in the future of C storage of Boreal peatlands. This study examined the impacts of fire on key environmental controls on CO2 fluxes at the plot‐scale (using static chambers) between burned and unburned understory vegetation throughout the growing season of 2017 in a treed fen impacted by the Horse River wildfire (2016) in Fort McMurray, Alberta, Canada. Both gross ecosystem productivity (GEP) and total respiration (Rtot ) were less at burned plots compared with unburned. Temporal patterns varied between the plots, where both component of CO2 fluxes at the unburned plots were largest in June, whereas at the burned plots, CO2 fluxes peaked in the late growing season. GEP and net ecosystem exchange (NEE) showed a positive relationship with depth of burn, with the deepest burned areas showing significantly greater CO2 uptake, coinciding with both increased bioavailable phosphorus and greater moss recolonization. At the unburned plots, soil temperature was a dominant control on CO2 fluxes. This work demonstrates the importance of the depth of burn to post‐fire carbon fluxes and how a knowledge of burn severity and depth can inform understanding of the recovery trajectory of northern peatlands following fire disturbance.